2D multichannel seismic reflection data of RV METEOR cruise M34/1, Cape Basin, profile AWI-96030 - Estella Weigelt; Gabriele Uenzelmann-Neben (PANGAEA, 2025)
The data set provides raw and processed seismic reflection data collected during Expedition M34/1 onboard RV Meteor in the Cape Basin in 1996. Detailed data acquisition parameters for the profiles are documented in the expedition report Wefer et al. 1997. Metadata, recording parameters, and the seismic data processing sequence are documented in the EBCDIC-Headers enclosed in the seg-y files. Navigation information is included in the seg-y headers, in the Shot-list files and Navigation files (see raw data). A ReadMe file additionally lists the metadata and recording parameters for each seismic profile. The data set is grouped into three categories: 1. Raw data comprise (a) demultiplexed seismic data in seg-y format, (b) a shot list of date, time and shot-number, and (c) navigation data with date, time, and coordinates. 2. Primary data consist of (a) CDP-sorted data in seg-y format, and (b) navigational data in a conventional UKOOA- file. 3. The data product is provided as migrated version of the seismic profile in seg-y format.